2019
DOI: 10.1021/acsbiomaterials.9b00270
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification by Divalent Main-Group-Elemental Ions for Improved Bone Remodeling To Instruct Implant Biofabrication

Abstract: Divalent main-group-elemental ions are widely used to improve osteogenic capacity of implants biofabricated from Ti and its alloys. However, the conclusions regarding their osseointegration and immunogenicity are always inconsistent because of the multiple bone remodeling processes as well as the distinct material surface features arising from processing. Here we successfully manufactured the porous micro/nanostructured surface topography with divalent main-group-elemental ions (Mg2+, Ca2+, Sr2+, Ba2+) on subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…[66] Modification of biological coating on its surface can increase its biological activity. [67] Bioceramics (phosphate, silicate, and bioactive glass) have good biological activity, especially for bone mineralization. [68,69] CNTs/carbon fibers can conduct electricity and regulate cell electrophysiological signals, and can be used in heart, [70] muscle, [71] and nerve tissue.…”
Section: Others-cell Supporting Materialsmentioning
confidence: 99%
“…[66] Modification of biological coating on its surface can increase its biological activity. [67] Bioceramics (phosphate, silicate, and bioactive glass) have good biological activity, especially for bone mineralization. [68,69] CNTs/carbon fibers can conduct electricity and regulate cell electrophysiological signals, and can be used in heart, [70] muscle, [71] and nerve tissue.…”
Section: Others-cell Supporting Materialsmentioning
confidence: 99%
“…Some researchers believe that Sr does not affect the number of initial adherent cell [83] but Gong et al have found that Sr-modified im-plants upregulate adhesion of MSCs. [75] Cell migration is closely associated with the effect of osteogenesis, especially for BMSCs. The GFP-labeled BMSCs migrated quickly on Sr-incorporated NTs surface than that on NTs.…”
Section: Sr-incorporated Coatingmentioning
confidence: 99%
“…Not reported [ 168] Ag-Ti alloy Reproduced with permission. [75] Copyright 2019, American Chemical Society.…”
Section: Human Osteoblastsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides nanotopographical cue, studies have also highlighted the significance of inorganic ions (such as Sr 2+ [ 22 , 23 ], Mg 2+ [ 24 , 25 ] and Zn 2+ [ 26 ]) in controlling polarization behavior of macrophages. Among these ions, Sr 2+ exhibits great potential in accelerating phenotypic transition of macorphages towards M2 compared to other inorganic ions [ 27 ]. For instance, Sr contained silica-based bioactive materials facilitated phenotypic transformation of macrophages towards M2 by the released Sr 2+ to secrete abundant platelet-derived growth factor-BB (PDGF-BB), enhancing angiogenesis and thus osseointegration [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%